Social capital and economic mobility in tourism: a systematic literature review - Norliza Aminudin; Salamiah A. Jamal (Cogent Social Sciences)
The existing literature mapping the state of social capital and economic mobility in tourism does not provide in-depth information concerning the post-pandemic challenge that caused a mismatch between them. Only a limited number of articles have attempted to systematically review available literature in this field, which has led to the current study, which aims to develop a systematic review related to social capital and economic mobility in tourism. The review encompassed 40 key journal articles from three reputable databases—Scopus, Science Direct, and Google Scholar—from 2006 to 2023. The 18 years were meticulously considered, and the review protocol adhered to the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Thematic analysis was applied to categorise the literature, resulting in four main themes: Community Development, Community Adaptation, Community Participation, and Quality of Life. This review presented several recommendations for social capital, stakeholders, and communities to consider in future.